A Comparative Study of Flat Slabs Using Different Shear Reinforcement Parameters - Girish, N; Lingeshwaran, N (International Journal of Engineering and Technology, 2018)
Punching shear failure is a brittle failure and it is one of the most important types of failure to be considered while designing a reinforced concrete flat slab. This paper aims to study the performance of reinforced concrete flat slabs equipped with different punching shear reinforcement parameters. Three flat slab specimens were cast where two specimens contain punching shear reinforcement in the form of shear stirrups and structural shearbands. The test specimens have length and width of 1000mm and thickness of 185mm for the slabs. The slabs are connected to a column at the center with length and breadth of 300mm and a depth of 700mm. The test specimens were supported by steel plates with length and breadth of 150mm and a thickness of 25mm at the four corners of the slab. The test specimens are loaded on the column face at the top. The deflection, strain and crack pattern were observed and recorded. Â Â